The Role of PAI Teachers in Managing Class Conflicts to Increase Social Empathy and Anti-Bullying Attitudes of Junior High School Students (Case Study in Junior High School in Pacitan District) - Hidayati, Fithri (Global Education Journal, 2025)
The phenomenon of bullying in the school environment is a serious problem rooted in low social empathy and students' inability to manage conflicts positively. The role of Islamic Religious Education Teachers (PAI) as central figures who teach noble moral values and compassion is crucial, especially through their example in dealing with dynamics and conflicts that occur in the classroom. This study aims to examine the extent to which the example of PAI teachers in managing classroom conflicts has a significant influence on increasing social empathy and forming anti-bullying attitudes in junior high school (SMP) students. This research is a qualitative approach with a type of case study research. The purpose of this research aims to fill the literature gap by proving that PAI teachers are key actors who use conflict management as a medium to form the character of students who empathize and reject violence. The results of the research of PAI teachers have a very important and strategic role in managing classroom conflicts to increase social empathy and foster anti-bullying attitudes.